Environment‐Specific Fluorescence Response of Microporous, Conformation‐Variable Conjugated Polymer Film to Water in Organic Solvents: On‐line Real‐Time Monitoring in Fluidic Channels. Issue 11 (22nd April 2014) - Han, Dong‐Cheul; Jin, Young‐Jae; Lee, Joong‐Heon; Kim, Shin‐Il; Kim, Hyo‐Jin; Song, Kyu‐Ho; Kwak, Giseop
<x xml:space="preserve">Abstract</x> Poly[1‐phenyl‐2‐(p‐trimethylsilyl)phenylacetylene] (PTMSDPA) with microporous and intramolecular stack structures in the bulk solid state can be used as a fluorescent water sensor for on‐line real‐time monitoring. A solubility parameter (δ) of PTMSDPA is estimated from the degree of swelling and solvation of the polymer in various organic solvents. When the PTMSDPA film is immersed in organic solvents with a range of δ values, the fluorescence (FL) intensity increases significantly due to swelling, whereas the FL intensity decreases gradually upon the addition of water in the solvents due to deswelling. The FL decreasing ratios are quite different according to the solvents. The hydrogen‐bonding strength of the solvents toward water plays a key role in determining the FL responsivity of the polymer. The FL response is very specific to water in organic solvents. The PTMSDPA film responds quickly to water within several seconds. A fluidic channel of which the inner wall is coated with PTMSDPA is fabricated to demonstrate the on‐line, real‐time monitoring of water in flowing solvents. The development of more facile and convenient devices, such as microfluidic lab‐on‐chip and optode sensors, using PTMSDPA as an active layer will advance practical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>